The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1111/j.1751-1097.1975.tb06682.x
|View full text |Cite
|
Sign up to set email alerts
|

THERMOLUMINESCENCE STUDIES ON SPINACH LEAVES AND EUGLENA

Abstract: Abstract— Spinach leaves and Euglena cells when frozen in light to 77 K emit light during slow warming in the dark to give 6 peaks. The peak appearing at 118 K is observed even after DCMU or heat treatment and also in aged chloroplasts that are inactive in electron transport. The data indicate that peaks appearing at 261 and 321 K are due to back reactions of primary acceptors of PS II and PS I respectively with oxidized chlorophylls. The DCMU sensitivity of Tl peaks at 283 and 298 K suggests that they are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Stainless steel planchet with 0.45 ml of chloroplast suspension was relaxed for 5min in the dark and then cooled from ambient temperature to liquid nitrogen temperature in the presence of fluorescent white light tubes of intensity 1.1Wm -2. Glow curves were recorded from the samples according to the method described earlier (see Desai et al 1975).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stainless steel planchet with 0.45 ml of chloroplast suspension was relaxed for 5min in the dark and then cooled from ambient temperature to liquid nitrogen temperature in the presence of fluorescent white light tubes of intensity 1.1Wm -2. Glow curves were recorded from the samples according to the method described earlier (see Desai et al 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 represents glow curves from DCMUtreated spinach chloroplasts following UV irradiation at ambient temperature. In the past, (Desai et al 1975, Sane et al 1977 we have shown that DCMU treatment inhibits glow peaks I and IV appearing at -36 and 25°C and enhances peaks II and V observed at -12 and 48°C. Very often, a small hump representing peak III at 10°C is observed in DCMU treated samples.…”
Section: Temperature (°C)mentioning
confidence: 99%
“…However, thermoluminescence studies provide support for some PSI luminescence. The peak appearing at 321K, called Peak V in the nomenclature of Desai et al [6], is not decreased by 3-(3,4-dichlorophenyl)-l,l-dimethylurea (DCMU), can be excited by far-red (e.g., 740nm) light, is enhanced in particles enriched in PSI, and retains one third of its yield after the heating of Euglena to 55 °C [20]: all consistent with the idea that the luminescence in peak V arises from PSI (However, see [ 11 ] ).…”
Section: Introductionmentioning
confidence: 99%
“…The six bands which we observed were denoted in [ 1,2] as Z, Z,, A, Br , Bs and C bands with partial modification of Arnold's nomenclature; in [3,4] the six bands were denoted as Z, I, II, III, IV and V. The A, Br and B2 bands were found to be closely related to the oxygenevolving activity of chloroplasts [S-7]. We have demonstrated that darkgrown green leaves of gymnosperm, dark-grown green cells of algae and angiosperm leaves greened under flashing light of long dark intervals of 30 s do not emit these three bands, unless the latent oxygen-evolving system in these leaves and cells is activated by continuous light or by short interval flashes of a few seconds apart [8,9] .…”
Section: Introductionmentioning
confidence: 99%